Barriers and facilitators influencing the sustainment of health behaviour interventions in schools and childcare services: a systematic review - Shoesmith, Adam (Implement Sci, 2021)
BACKGROUND: Sustainment has been defined as the sustained use or delivery of an intervention in practice following cessation of external implementation support. This review aimed to identify and synthesise factors (barriers and facilitators) that influence the sustainment of interventions (policies, practices, or programmes) in schools and childcare services that address the leading risk factors of chronic disease. METHODS: Seven electronic databases and relevant reference lists were searched for articles, of any design, published in English, from inception to March 2020. Articles were included if they qualitatively and/or quantitatively reported on school or childcare stakeholders’ (including teachers, principals, administrators, or managers) perceived barriers or facilitators to the sustainment of interventions addressing poor diet/nutrition, physical inactivity, obesity, tobacco smoking, or harmful alcohol use. Two independent reviewers screened texts, and extracted and coded data guided by the Integrated Sustainability Framework, an existing multi-level sustainability-specific framework that assesses factors of sustainment. RESULTS: Of the 13,158 articles identified, 31 articles met the inclusion criteria (8 quantitative, 12 qualitative, 10 mixed-methods, and 1 summary article). Overall, 29 articles were undertaken in schools (elementary n=17, middle n=3, secondary n=4, or a combination n=5) and two in childcare settings. The main health behaviours targeted included physical activity (n=9), diet (n=3), both diet and physical activity (n=15), and smoking (n=4), either independently (n=1) or combined with other health behaviours (n=3). Findings suggest that the majority of the 59 barriers and 74 facilitators identified to impact on intervention sustainment were similar across school and childcare settings. Factors predominantly relating to the ‘inner contextual factors’ of the organisation including: availability of facilities or equipment, continued executive or leadership support present, and team cohesion, support, or teamwork were perceived by stakeholders as influential to intervention sustainment. CONCLUSIONS: Identifying strategies to improve the sustainment of health behaviour interventions in these settings requires a comprehensive understanding of factors that may impede or promote their ongoing delivery. This review identified multi-level factors that can be addressed by strategies to improve the sustainment of such interventions, and suggests how future research might address gaps in the evidence base. TRIAL REGISTRATION: This review was prospectively registered on PROSPERO: CRD42020127869, Jan. 2020. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13012-021-01134-y.